Autonomic flap damping mechanisms for utility based service selection - Bourcier,J; McCann,J (2010)
The service oriented computing paradigm can be described as consisting of the following major components: service providers, service consumers and one or more service trader. One of the most challenging problems in this field has surrounded the choice of service provider in the presence of several, that best matches the consumer requirements. There has been a body of work exploring quality measures as a means of discerning between services. However, in much of the previous work the service selection remains relatively static during the life-time of the session, yet finer-granularity is required by Pervasive applications to drive their self-configuration, repair and management. Therefore how subtle changes in service quality affect the service choice, and ultimately the system's optimal performance in terms of its goals, is less well understood. In this paper, we propose a utility-function driven framework that dynamically chooses the most suitable providers for each consumer; driving self-optimization. We evaluate the performance and accuracy of our solution by implementing a pervasive home video application. Our results show our framework imposes minimal overheads while offering good response time and an accurate choices to the provider. Further, we observe that under less stable conditions, the framework state-flaps quite severely, producing oscillations between consumer-service bindings; increasing overheads. To this end, we have established several mechanisms that minimize the number of oscillations under unstable conditions and have evaluated each in terms of their ability to maintain stability under differing degrees of volatility. © 2010 IEEE.